Comparative analysis of single and two DOF controllers for integrating and time-delay processes. (1st January 2013) - Saravanakumar, G.; Kannan, G.; Mahalik, N.P.
In all process industries, the system with feedback nature should satisfy desirable dynamic and steady state response characteristics for given test signals for which the effect of disturbances should be minimum and set point tracking should be smooth and rapid. Also, the insensitiveness to parameter variations with all acceptable dynamic characteristics cannot be met when system is with single controller. This can be met with the two degrees of freedom (2-DOF) controller which can enhance the above aspects, particularly for integrating processes with longer time delay. In this proposed method the process transfer function is developed into an infinite Taylor series which consists of time-weighted integrals of the process impulse response. The moments can be obtained by calculating repetitive (multiple) integrals of the process input (u) and output (y) signals during the change of the process steady-state. The method used for tuning the 2-DOF controller is the magnitude optimum multiple integration. The control loop robustness and performance indices are also experimented by comparing the responses of the processes having 1-DOF controller tuned by popular tuning methods to show the effectiveness of 2-DOF controller qualitatively.